Critical Readings of The Salesman in Iran - Jamshidi,Akram (2018)
Asghar Farhadi's cinema has found a worldwide audience in recent years, and most of his movies have been globally celebrated. His most recent movie The Salesman, however, has had a dialectical existence in his own homeland. The nature of this controversy reveals up a number of dominant social issues in contemporary Iran. Accordingly, Iranian could be divided into supporters and critics of Farhadi's The Salesman. The former believe that it is about social problems and in association with Farhadi's cinema. The latter see it as his attempt for international celebration even to the point of dishonoring his homeland. This essay offers two contrasting readings of Asghar Farhadi's The Salesman by the Iranian film reviewers and critics. Data collection includes texts which were taken from the most leading cinematic publications, websites and TV shows.